2010
DOI: 10.1002/psp.630
|View full text |Cite
|
Sign up to set email alerts
|

Critical approaches to transit migration

Abstract: This article introduces the subject of this special issue and presents the papers that follow. It traces the origins of the label ‘transit migration’ to discussions of what was called the ‘new migration’ in the early 1990s. These migrations related to the particular geopolitical context at the end of the Cold War. Though they established the pre‐emptive rationale whereby concern is focused as much on potential migration as on actual movement, there have been four substantial changes since then. As the geopolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(78 citation statements)
references
References 10 publications
1
69
0
8
Order By: Relevance
“…In migrant mobility studies, ample scholarly accounts have shown that it is too simplistic to think of migration in linear terms, starting with migrants leaving a sending state, going through their arriving in a host-state, and ending with their integration or assimilation in a host-state (Meeus 2012;Robertson 2014). By now it has been acknowledged that migrants can spend years in transit without having their temporary status resolved (Collyer, Düvell, and de Haas 2012). Their lives can evolve around single or multiple loops of circular migration, considered bringing a 'triple win solution' of benefits to sending, host-states, and migrants themselves (Wickramasekara 2011;Triandafyllidou 2013).…”
Section: Focus On Context: Spatial and Temporal Dimensionsmentioning
confidence: 99%
“…In migrant mobility studies, ample scholarly accounts have shown that it is too simplistic to think of migration in linear terms, starting with migrants leaving a sending state, going through their arriving in a host-state, and ending with their integration or assimilation in a host-state (Meeus 2012;Robertson 2014). By now it has been acknowledged that migrants can spend years in transit without having their temporary status resolved (Collyer, Düvell, and de Haas 2012). Their lives can evolve around single or multiple loops of circular migration, considered bringing a 'triple win solution' of benefits to sending, host-states, and migrants themselves (Wickramasekara 2011;Triandafyllidou 2013).…”
Section: Focus On Context: Spatial and Temporal Dimensionsmentioning
confidence: 99%
“…Another important shift in the nature of migrant entry practices was an increase in people arriving with EU passports from 2000 onwards through a process of 'transit migration' (Collyer, Düvell, and De Haas 2010). EU citizenship emerged as essential in the formation of complex transnational social spaces among Latin Americans with regularisation being a core element in their construction as civic capital was accumulated and converted and citizenship attained (McIlwaine 2012).…”
Section: Creating Webs Of (Ir)regularity: Migrant Entry and Regularismentioning
confidence: 99%
“…Transit migration is a highly debated topic in policy arenas and academia (Düvell 2006;Collyer, Düvell and de Haas 2012;Papadopoulou-Kourkoula 2008). In general, this debate has a simplistic and linear understanding of migration as if migrants depart, go through a transit phase, and settle afterwards (see for similar critical comments Collyer, Düvell and de Haas 2012).…”
Section: On the Road: African Stepwise Migration Towards The Eumentioning
confidence: 99%